Implementation of WYSIWYG in the Development of ITCC ITPLN Letter Management Information System - Herman Bedi Agtriadi; Jatnika, Hendra; Yessy Fitriani; Zakiya Viantika Sihabudin4; Muhammad Nur Khanib; David Gabriel Sembiring; Ocha Nia Martcya Situmorang (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2021)
Information Technology Certification Center (ITCC) is a laboratory focused on Certification activities in Information and Technology. Currently, ITCC uses a manual system with Microsoft Excel for creating letter numbers, which is time-consuming and prone to data loss due to unintegrated storage. To solve this, the author developed a letter archive application using the Rapid Application Development (RAD) model, which accelerates the development process by producing incremental software versions. This application improves the efficiency of numbering and securely storing mail archives while providing a WYSIWYG editor for easy document editing